Experimental investigations of planar millimeter-wave antenna array - Antonov, A. S.; Kostikov, G. A.; Lubina, L. M.; Savelev, V. A.; Ballandovich, S. V.; Sugak, M. I. (2015 IEEE NW Russia Young Researchers in Electrical and Electronic Engineering Conference (EIConRusNW), 2015)
Results of development and full-wave simulation of millimeter-wave antenna array based on inhomogeneity planar dielectric waveguide are presented. Model of antenna array was made and results of experimental investigations of radiation pattern and gain are presented. Investigations of amplitude and phase distributions of antenna array in the near field zone were carried.